Spectral thresholds in macular degeneration. Issue 8 (August 1983) - Alvarez, S L; King-Smith, P E; Bhargava, S K
Abstract : Spectral sensitivities were measured in 18 normal eyes, 9 eyes in patients with senile macular degeneration, 4 patients with Stargardt's juvenile macular degeneration (JMD), and 2 patients without conclusive signs–that is, genetic or morphological abnormalities–to indicate the cause of loss of central vision. Spectral sensitivity, testing for which included measurements on white, yellow, purple, and blue backgrounds, is here used as an aid in differential diagnosis for cases of macular degeneration.